Development of a photo-baffled reactor for microalgae-nitrifying bacteria consortia: Achieving long-term, stable partial nitrification. Issue 5 (October 2021) - Watari, Takahiro; Fukushima, Yoshiki; Miwa, Toru; Hirakata, Yuga; Kawakami, Shuji; Nakamura, Yoshinobu; Hatamoto, Masashi; Yamaguchi, Takashi
Abstract: In this study, a photo-baffled reactor was operated to assess the performance of microalgal-nitrifying bacteria consortia in treating ammonia with its input concentration up to 180 mg-N·L −1 . The six-compartment reactor, with a total effective volume of 3.2 L, was run continuously for 350 days at 30 °C. Overall, 66 ± 11% of ammonia was removed at a nitrogen loading rate of 0.083 ± 0.011 kg-N·m −3 ·day −1 . In addition, long-term, stable partial nitrification was confirmed with nitrite concentration of 60 ± 26 mg-N·L −1 in effluent. On days 200 and 350, due to inhibition from the nitrite-oxidizing bacteria (NOB) activity, the dissolved oxygen and the free ammonia concentration was recorded as low as 0.3–0.7 mg·L −1 and 14–24 mg-N·L −1 in each column, respectively. The special configuration of the photo-baffled reactor created a competitive environment between Chlorella vulgaris and nitrifying bacteria. The microbial community structure of the retained sludge indicated that although detected at only 2–3% upstream, ammonia-oxidizing bacteria Nitrosomonas europaea increased downstream of the reactor. Meanwhile, the detection rate of NOB was less than 0.05% in each column and based on quantitative polymerase chain reaction analysis, NOB growth was inhibited. Therefore, these microalgae-nitrifying bacteria consortia have the potential to be a novel partial nitrification process for post-treatment using the anammox process. Graphical Abstract: ga1 Highlights: A photo-baffled reactor with microalgal-nitrifying bacteria consortia was run. The system has shown great potentials for ammonium removal. Long-term stable partial nitrification was observed in the reactor. The low dissolved oxygen and the free ammonia level may inhibit NOB growth.